Effects of metabolic engineering on downstream processing operational cost and energy consumption : the case of Escherichia coli's glycerol conversion to succinic acid (2017)
BACKGROUND Currently, the criteria for selection of gene targets in strains oriented to fermentation-based bioprocesses development have been largely based on the bioproduct yield, concentration or productivity. Nevertheless the concentration and purification of the product of interest strongly influences the final production cost. Then, a metabolic engineering-downstream coupling evaluation would be central when selecting the metabolic pathways candidates in the strain. Here, we evaluated the effects of the metabolic engineering an Escherichia coli strain in a succinic acid (SA) fermentation process using glycerol on the downstream process in terms of operational cost and energy consumption. RESULTS Three strain scenarios were selected using a bi-level linear optimization problem solved by MILP, and simulated in a transient fashion with dynamic flow balance analysis considering both biomass and SA productivity. Our results show that the succinic acid productivity constitutes a central parameter when selecting the appropriate gene targets for deletion nonetheless the presence of organic acids in the downstream...